On Coming After : Studies in Post-Classical Greek Literature and its Reception. - Hunter, Richard (Trends in classics. Supplementary volumes., 2009)
This book gathers together many of the principal essays of Richard Hunter, whose work has been fundamental in the modern re-evaluation of Greek literature after Alexander and its reception at Rome and elsewhere. At the heart of Hunter?s work lies the high poetry of Ptolemaic Alexandria (Callimachus, Theocritus, and Apollonius of Rhodes) and the narrative literature of later antiquity (?the ancient novel?), but comedy, mime, didactic poetry and ancient literary criticism all fall within the scope of these studies. Principal recurrent themes are the uses and recreation of the past, the modes of.